Beispiel Nr: 23
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 2x +2y =1\frac{7}{10}\\ 3x +6y = 3 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 2 x +2 y =1\frac{7}{10}\\ II \qquad 3 x +6 y = 3 \\ \text{I nach x auflösen}\\ 2 x +2 y =1\frac{7}{10} \\ 2 x +2 y =1\frac{7}{10} \qquad /-2 y\\ 2 x =1\frac{7}{10} -2 y \qquad /:2 \\ x =\frac{17}{20} -1 y \\ \text{I in II}\\ 3 (\frac{17}{20} -1 y ) + 6 y = 3 \\ 2\frac{11}{20} -3 y +6 y = 3 \qquad / -2\frac{11}{20} \\ -3 y +6 y = 3 -2\frac{11}{20} \\ 3 y = \frac{9}{20} \qquad /:3 \\ y = \frac{\frac{9}{20}}{3} \\ y=\frac{3}{20} \\ x =\frac{17}{20} -1 y \\ x =\frac{17}{20} -1 \cdot \frac{3}{20} \\ x=\frac{7}{10} \\ L=\{\frac{7}{10}/\frac{3}{20}\} \end{array} & \begin{array}{l} I \qquad 2 x +2 y =1\frac{7}{10}\\ II \qquad 3 x +6 y = 3 \\ \text{I nach y auflösen}\\ 2 x +2 y =1\frac{7}{10} \\ 2 x +2 y =1\frac{7}{10} \qquad /-2 x\\ 2 y =1\frac{7}{10} -2x \qquad /:2 \\ y =\frac{17}{20} -1x \\ \text{I in II}\\ 3x + 6(\frac{17}{20} -1 x ) = 3 \\ 5\frac{1}{10} -6 x +6 x = 3 \qquad / -5\frac{1}{10} \\ -6 x +6 x = 3 -5\frac{1}{10} \\ -3 x = -2\frac{1}{10} \qquad /:\left(-3\right) \\ x = \frac{-2\frac{1}{10}}{-3} \\ x=\frac{7}{10} \\ y =\frac{17}{20} -1 x \\ y =\frac{17}{20} -1 \cdot \frac{7}{10} \\ y=\frac{3}{20} \\ L=\{\frac{7}{10}/\frac{3}{20}\} \end{array} \end{array} $